Strategi Pengembangan Bisnis Mental Healthiness Event Organizer Berbasis Analisis SWOT dan Business Model Canvas - Khusna, Siti Lailatul; Utami, Dati Mega; Nurunnisa, Ika Amalia; Kusuma, Aditya Indra; Khaerani, Anisa Zahra; Novitaningtyas, Ivo (Jurnal Nasional Manajemen Pemasaran dan SDM, 2023)
Mental health is quite an interesting issue and is discussed by the public. Several cases in Indonesia show the phenomenon that students tend to be prone to mental health problems such as stress, anxiety and depression. Based on these conditions, the Mental Healthiness Event Organizer business opportunity can be developed. This article aims to identify the internal and external conditions of the Mental Healthiness Event Organizer business and formulate a business development strategy, specifically in the study of Arcadia Tesi. SWOT analysis is used to identify the conditions of internal factors and external factors. The results of the analysis show a strategy formulation that can be applied to develop a business model based on the business model canvas. The results show several strategies that can be implemented by Arcadia Tesi, such as establishing strategic alliance partnerships with the mental health community, educational institutions and other institutions, diversifying products according to the needs of potential partners, emphasizing points of differentiation and unique selling points that differentiate them from competitor products, maximizing online and offline marketing communications, as well as operational cost efficiency. The results provide managerial implications for entrepreneur Mental Healthiness Event Organizer Arcadia Tesi to develop their business, as well as becoming reference material for further research.